Creating Integrated Science and Language Arts Centers: Considering Ocean Literacy and the 5E Instructional Model. Issue 1 (16th December 2022) - Hamilton, Frances; Skelley, Dana
Unfortunately, most lower elementary grades teach little to no science content due to a primary focus on language arts and math instruction. Therefore, this article focuses on the importance of integrating science with language arts and shares steps on creating stations within an effective integrated science and language arts learning center. The example given was developed to aid in elementary students' understanding of aquatic animals, specifically using seashells to explore the world of mollusks. Stations within the center are described in detail and supporting documents from student outcomes are included. In addition, an explanation of where the center is used in the 5E Instructional Model learning sequence is discussed. This outline of a completed center provides classroom teachers or non-traditional educators insight into the cognitive process for making one and can be applied to any topic for integration of science and language arts.